The elderly assisted in an Emergency Care Unit: The perception of the nursing team (Research, Society and Development, 2023)
Objective: To evaluate the perception of the nursing team regarding the care provided to the elderly in an Emergency Care Unit. Method: This is a study with a qualitative approach of the descriptive exploratory type. 20 nursing professionals participated. For data collection, a semi-structured interview was used. Data analysis was based on the Content Analysis technique, thematic category. Data collected through semi-structured interviews was analyzed using the content analysis technique proposed by Bardin. Results: the category “Unveiling the elderly in the light of health professionals from an urgency and emergency unit” emerged. The professionals’ understanding of care for the elderly focused essentially on biological perspectives. Changes resulting from the aging process were used as a justification for family neglect or abandonment. Conclusion: The need for permanent education with nursing professionals about the aging process and the biopsychosocial issues that it involves is reiterated, with the perspective to enable changes in the conception of the Elderly Person, favoring comprehensive care for this population group.